Psychosocial care for children with haemophilia and their parents in the Netherlands. Issue 3 (21st March 2017) - Limperg, P.F.; Haverman, L.; Beijlevelt, M.; van der Pot, M.; Zaal, G.; de Boer, W.A.; Fijnvandraat, K.; Peters, M.; Grootenhuis, M. A.
Abstract : Introduction: Children growing up with haemophilia are at greater risk for psychosocial problems than their healthy peers. Providing psychosocial care to children with haemophilia and their families is indispensable, since psychosocial factors can have a significant impact on health and health‐related quality of life (HRQOL). Aims: Our aim was to give a description of psychosocial care provided by the multidisciplinary team of the Hemophilia Comprehensive Care Centre (HCCC) at the Emma Children's Hospital in Amsterdam, the Netherlands. With this overview, other caregivers and hospitals can benefit in organizing their psychosocial care for children with haemophilia. Methods: The focus of the psychosocial care provided by the multidisciplinary team is on preventing psychosocial problems and medical‐related stress, and supporting and equipping the child with haemophilia and its parents with as many skills as possible to lead an independent life with a high HRQOL. Results: Core elements of the psychosocial care are therefore monitoring and screening of HRQOL (e.g. in daily clinical practice viawww.hetklikt.nu ), psychoeducation (haemophilia camp, haemophilia school, disease‐specific activities, meetings for girls, parent meetings), practical help (Emma at Work, an employment agency for adolescents and young adults; Educational Facility and school visits), psychosocial interventions (the On Track group intervention and the Haemophilia Coping and Perception Test) and individual care (psychological counselling and referrals). Conclusion: By providing this overview of psychosocial support offered and by sharing this knowledge, psychosocial care can become more structured and consistent between HCCCs around the world. Potentially, processes and outcomes of care can be improved.